ANTIDIABETIC, ANTI-INFLAMMATORY, ANTIBACTERIAL, ANTI-HELMINTHIC, ANTIOXIDANT AND NUTRITIONAL POTENTIAL OF MUSA PARADISIACA - OLUWAFEMI OMONIYI OGUNTIBEJU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
The medicinal and economic values of medicinal plants remain vital to the well-being, growth, and development of humans, especially those living in developing countries. It has been shown that due to the availability, less side effects, general acceptance by local people, medicinal plants contribute significantly to improving health-care delivery system by supplying important pharmaceutical and pharmacological ingredients that are affordable to the teaming majority of people. It is estimated that 30% of pharmaceutical products that are sold globally is rich in compounds derived from plant materials. It is also of interest to report that over 80% of the people in developing countries, mostly in Asia and Africa depend heavily on plant products in the treatment and management of various disease conditions. The interest in demand and utilization of medicinal plants has also increased significantly due to the high cost of orthodox medications, lack of good transportation, lack of storage facilities, inadequate availability of health professionals, and lack of the will and political power to provide basic health needs for the citizens of these developing countries. Musa paradisiaca is one of such medicinal plants believed to have multi-faceted health benefits and its health benefits extend to different countries of the world. It is a stable crop found in Asia, Africa, and Central and South America commonly consumed as energy-yielding food but with many medicinal values as well. It is used in the treatment and management of diabetes mellitus, inflammation, parasitic infection, microbial infections, renal, and liver dysfunction. This manuscript focuses on the antidiabetic, antioxidant, anti-inflammatory, antimicrobial, anti-helminthic, and nutritional values of M. paradisiaca.